Re-Treatment of Class I Malocclusion Bimaxillary Protrusion with Anterior Crowding: Case Report - Habar, Eddy H. (Journal of Case Reports in Dental Medicine, 2021)
Objective: This article discusses a case report of Class I malocclusionÂ  bimaxillary protrusion with anterior crowding that re-treated.Methods: Female patient aged 23 with complaints of unfinished treatment and unsatisfactory results on previous treatments. The objectiveÂ  examination showed edentulous in 14, 24 34 and 44, crossbite teeth 13 and 43, and anterior crowding. Patient profile is convex.Result: Orthodontic treatment with fixed orthodontic appliances to correct crossbite and close the extraction space.Conclusion: Maximum results are obtained with appropriate treatment.